Nanoparticle Analysis in Biomaterials Using Laser Ablation−Single Particle−Inductively Coupled Plasma Mass Spectrometry - Metarapi, Dino; Šala, Martin; Vogel-Mikuš, Katarina; Šelih, Vid S; van Elteren, Johannes T (Analytical chemistry (Washington), 2019)
In the past decade, the development of single particle–inductively coupled plasma mass spectrometry (SP-ICPMS) has revolutionized the field of nanometallomics. Besides differentiation between dissolved and particulate metal signals, SP-ICPMS can quantify the nanoparticle (NP) number concentration and size. Because SP-ICPMS is limited to characterization of NPs in solution, we show how solid sampling by laser ablation (LA) adds spatial-resolution characteristics for localized NP analysis in biomaterials. Using custom-made gelatin standards doped with dissolved gold and commercial or synthesized gold nanoparticles, LA-SP-ICPMS conditions such as laser fluence, beam size, and dwell time were optimized for NP analysis to minimize NP degradation, peak overlap, and interferences from dissolved gold. A data-processing algorithm to retrieve the NP number concentration and size was developed for this purpose. As a proof-of-concept, a sunflower-root-sample cross-section, originating from a sunflower plant exposed to gold NPs, was successfully imaged using the optimized LA-SP-ICPMS conditions for localized NP characterization.